FLOW PATTERNS AND PRESSURE DROP OF TWO-PHASE FLOW IN HORIZONTAL CAPILLARY - Mehdi, M. S.; Chughtai, I. R.; Inayat, M. H. (The Nucleus, 2020)
Hydrodynamics behavior for two-phase flow was studied in horizontal capillary tube 3mm diameter for monolith reactor. Gas used was air while the liquid phase was water. Different flow patterns were observed for a range of gas and liquid flow rates. Pressure drop was measured across the whole length of tube. Effect of flow rates on bubble length was observed by photographic technique. It was found that pressure drop increases with increasing flow rate of liquid and it showed less dependency on gas flow rate. A correlation has been proposed for pressure drop using these results. It was also observed that Bubble length increases with increasing flow rate of gas.